CAG Expansions Are Genetically Stable and Form Nontoxic Aggregates in Cells Lacking Endogenous Polyglutamine Proteins - Ashley A. Zurawel (American Society for Microbiology, 2016)
ABSTRACT Proteins containing polyglutamine (polyQ) regions are found in almost all eukaryotes, albeit with various frequencies. In humans, proteins such as huntingtin (Htt) with abnormally expanded polyQ regions cause neurodegenerative diseases such as Huntington’s disease (HD). To study how the presence of endogenous polyQ aggregation modulates polyQ aggregation and toxicity, we expressed polyQ expanded Htt fragments (polyQ Htt) in Schizosaccharomyces pombe. In stark contrast to other unicellular fungi, such as Saccharomyces cerevisiae, S. pombe is uniquely devoid of proteins with more than 10 Q repeats. We found that polyQ Htt forms aggregates within S. pombe cells only with exceedingly long polyQ expansions. Surprisingly, despite the presence of polyQ Htt aggregates in both the cytoplasm and nucleus, no significant growth defect was observed in S. pombe cells. Further, PCR analysis showed that the repetitive polyQ-encoding DNA region remained constant following transformation and after multiple divisions in S. pombe, in contrast to the genetic instability of polyQ DNA sequences in other organisms. These results demonstrate that cells with a low content of polyQ or other aggregation-prone proteins can show a striking resilience with respect to polyQ toxicity and that genetic instability of repetitive DNA sequences may have played an important role in the evolutionary emergence and exclusion of polyQ expansion proteins in different organisms. IMPORTANCE Polyglutamine (polyQ) proteins encoded by repetitive CAG DNA sequences serve a variety of normal biological functions. Yet some proteins with abnormally expanded polyQ regions cause neurodegeneration through unknown mechanisms. To study how distinct cellular environments modulate polyQ aggregation and toxicity, we expressed CAG-expanded huntingtin fragments in Schizosaccharomyces pombe. In stark contrast to many other eukaryotes, S. pombe is uniquely devoid of proteins containing long polyQ tracts. Our results show that S. pombe cells, despite their low content of endogenous polyQ proteins, exhibit striking and unexpected resilience with respect to polyQ toxicity and that genetic instability of repetitive DNA sequences may have played an important role in the emergence and expansion of polyQ domains in eukaryotic evolution.